The influence of networks, reputation, government support and export barriers on export performance of Malaysian exporters of halal products - Guo, Lei (2010)
This paper aims to investigate the extent to which factors such as business networks,company reputation, government support, and export barriers affect the export performance of exporting companies. Data for this study was obtained from a cross sectional study of Malaysian companies exporting halal products using a self-administered survey questionnaire. Based on a sample of 37 survey respondents, regression analyses were used to analyze the data. Results of the analyses showed that the level of export performance of the exporting companies in the sample is moderate. The influence of business networks on export performance is found to be positive and significant while the influence of foreign country export barriers on export performance is negative and significant. It is also interesting to note that certification practices of these companies tend to moderate the relationships between export performance and the factors: networks, reputation, home government support, and export barriers (including home and foreign country). Implications of this study are discussed and suggestions for future research are provided.